(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Purpose To study the hypoglycemic effect of ethanolic extract of Hedychium coronarium Linn. rhizome in alloxan induced diabetes in rat model. Methods The preliminary photochemical studies were carried out on the crude extract and the various chemical constituents present in the crude extract were evaluated. Acute toxicity studies as per OECD-23 guidelines to determine the safety doses of the root extract were carried out on male wistar strain of Albino rats. The various factors such as body weight, feed intake, blood glucose and serum insulin were regularly studied and evaluated. Results The hypoglycemic effect of ethanolic extract of Hedychium coronarium Linn. rhizome was studied on the various factors such as body weight, blood glucose levels of the alloxan induced diabetic rat model. Conclusion In present study administration of Hedychium coronarium Linn. rhizome extract produced a significant reduction in blood glucose, serum insulin, serum catalase and haemoglobin in alloxan induced rats. However, it seems promising that if this data will be validated in the future clinical trials, Hedychium coronarium rhizome extract may offer an alternative treatment for diabetes.